PERTUMBUHAN BEBERAPA VARIETAS PEPAYA (Carica papaya L.) PADA BERBAGAI JENIS PUPUK - Yohanis Tambing; Muhardi Muhardi; Dewa Ariembawa (Agroland: Jurnal Ilmu-ilmu Pertanian, 2010)
The research aimed to identify the growth of some papaya varieties as affected by various fertilizer applications. The research was carried out from November 2008 to March 2009 in "Puspita Karya Karava Tandau" Sidondo of Sigi Regency.  The research used a Split Plot Design.  The main plot was various papaya varieties (V): small local (v1), big local (v2), item (v3), watermelon (v4), Mexico (v5), and Bangkok (v6). The sub plot was fertilizer types (P): control (p0), Saputra Nutrient (p1), NPK (p2), bokashi (p3), Saputra nutrients + NPK (p4), and Saputra nutrient + bokashi (p5). The results of research indicated that only the manure types had significant effect on the growth of papaya.  The mixture of saputra nutrient+bokasi resulted in significantly larger plant stem diameter at 16 months after planting (MAP), height at 18 MAP, and dry weight than any other treatments.